Femoroacetabular impingement and classification of the cam deformity: the reference interval in normal hips - Pollard, Thomas CB (Informa Healthcare, 2010)
BACKGROUND AND PURPOSE: Most patients with femoroacetabular impingement (FAI) have a cam deformity, which may be quantified by measuring the alpha angle and anterior offset ratio (AOR). Knowledge of what constitutes a “normal” alpha angle and AOR is limited. We defined the reference intervals of these measurements from normal hips in the general population. PATIENTS AND METHODS: 157 individuals from the general population were reviewed clinically and radiographically. 74 individuals with clinical evidence of hip disease or radiographic evidence of osteoarthritis (OA) were excluded, leaving a study group of 83 individuals (mean age 46 (22–69) years, 44 females) with normal hips. The alpha angles and AORs were measured from cross-table lateral radiographs taken in 15° internal rotation. A validation study consisting of a cadaver study and a measurement reliability study was also performed. RESULTS: The mean alpha angle was 48° in men and 47° in women. The mean AOR was 0.19, the same in men and women. Thus, sexes were combined to derive 95% confidence intervals for the population mean alpha angle (46–49°) and AOR (0.18–0.20). The 95% reference interval for the alpha angle was 32–62° degrees, and for the AOR it was 0.14–0.24. The validation study confirmed that these measurements were resistant to a reasonable degree of variation in positioning and that the repeatability and reproducibility of the measurements was good. INTERPRETATION: These reference intervals indicate that clinically and radiographically normal hips may have alpha angles and AORs that have previously been considered “abnormal”. The thresholds provided by this study will aid classification of individuals involved in longitudinal studies of FAI and OA, and may be of use to the practicing clinician in evaluating the young adult with hip pain.